Relationship between longitudinal changes in step parameters and running economy in well-trained distance runners - Tanji, F.; Nabekura, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
Step parameters are associated with running economy (RE), but the relationship between these longitudinal changes remains unclear. In the present study, we aimed to clarify the relationship between changes in step parameters and RE at intensities below and above the lactate threshold (LT) in well-trained middle to long-distance runners and to acquire knowledge applicable to coaching. A total of 29 male university students training in distance running (age, 19.4 ± 1.0 yr; height, 171.3 ± 4.5 cm; body weight, 57.1 ± 3.6 kg) participated in the study. Participants performed multistage incremental treadmill tests to measure step parameters (ground contact time: CT; step length: SL; step frequency: SF; leg stiffness: kleg) and RE before and after 4 months of training. Since the LT speed of participants was 16.6 ± 1.1 km/h-1, intensities below, near, and above the LT were set at 13.8 and 15.0 km/h-1, 16.2 km?h-1, and 17.4 and 18.6 km/h-1, respectively. No significant relationships were observed between changes in RE and any of the step parameters at intensities below and near the LT. Moreover, although no significant relationship was noted between changes in RE and both SL and SF, there was a significant positive and negative relationship between changes in RE and CT and kleg, respectively, at intensities above the LT. Changes in kleg showed a strong negative correlation with CT changes at each intensity. It can be concluded from these findings that shortening the CT improves the RE for high-intensity running and that this variation is partly attributable to the improvement in kleg.